Impact of urine osmolality/urine sodium on the timing of diuretic phase and non-invasive ventilation support: Differences from late preterm to term neonates - Yu-Hsuan Chien; Yi-Ling Chen; Li-Yi Tsai; Shu-Chi Mu (Pediatrics and Neonatology)
Background: Extracellular fluid retained in the lungs lead to respiratory distress in both late preterm (LP) and term neonates. The relationship between urine parameters toward the diuresis and the duration of ventilation postnatally is unknown. To find the correlation between the diuretic phase with urine parameters in the first 4 days after birth and the duration of non-invasive ventilation (NIV). Methods: Serial measurements of urine osmolality (Uosm), urine sodium (UNa), and urine output (U/O) in neonates were collected at 5 time periods (T1:0–12 postnatal hours, T2:12–24 postnatal hours, T3:24–48 postnatal hours, T4:48–72 postnatal hours, T5:72–96 postnatal hours) were recorded. The correlations were analyzed in late preterm and term neonates. Results: Ninety-seven neonates were included. Negative correlation between Uosm and U/O were observed. LP neonates (n=26) and term neonates (n=71) had differences with Uosm at T2, UNa at T4, T5, and U/O at T2, T3. Factors of U/O < 1 ml/kg/hr at T1 (odds ratio (OR) = 20.0; 95% confidence interval (CI) 1.796-222.776; p = 0.015) or Uosm > 273 mOsm/L at T1 (OR = 9.0; 95% CI 1.031-78.574; p = 0.047) in LP neonates and UNa > 26.5 mEq/L at T5 (OR = 23.625; 95% CI 2.683-79.276; p < 0.01) in term neonates were associated with prolonged NIV use (> 120 hours). Conclusion: We speculate the significant correlation between Uosm/UNa and the diuretic phase. The LP neonates acquire earlier diuretic phase than the term neonates. The Uosm/UNa in the first few postnatal days had the correlation with the duration of NIV support. Keywords: Diuretic phase, Neonate, Non-invasive ventilation, Urine osmolality, Urine sodium